ANALISIS KERJA WANITA PETANI PADI DI KECAMATAN PIDIE KABUPATEN PIDIE - Raihani - (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2011)
This study aims to determine the activities will be undertaken by a woman who worked as rice farmers in the district of Pidie and determine the pattern of working hours of women working as rice farmers in the district of Pidie. The study population was female rice farmers in the district of Pidie. Given the population that much, then researchers took the women rice farmers in the district of Pidie as many as 40 people sampled in this study. The data was collected by spreading questionnaire and observation and data processing method using a percentage formula. Based on the results of research that has been done can be concluded that the type of work outside the hours of farming respondents were household activities (reproduction), looking for additional income, basic activities and social events. The pattern of working hours to activities highest respondent base is 8 hours, both household activities that is 5.5 hours, all three activities seek additional revenue that is 3 hours and for social activities is 0.5 hours. Key words: working hours, women rice farmers